Interaction between sugar and abscisic acid signalling during early seedling development in Arabidopsis - Dekkers, Bas J. W. (Springer Netherlands, 2008)
Sugars regulate important processes and affect the expression of many genes in plants. Characterization of Arabidopsis (Arabidopsis thaliana) mutants with altered sugar sensitivity revealed the function of abscisic acid (ABA) signalling in sugar responses. However, the exact interaction between sugar signalling and ABA is obscure. Therefore ABA deficient plants with constitutive ABI4 expression (aba2-1/35S::ABI4) were generated. Enhanced ABI4 expression did not rescue the glucose insensitive (gin) phenotype of aba2 seedlings indicating that other ABA regulated factors are essential as well. Interestingly, both glucose and ABA treatment of Arabidopsis seeds trigger a post-germination seedling developmental arrest. The glucose-arrested seedlings had a drought tolerant phenotype and showed glucose-induced expression of ABSCISIC ACID INSENSITIVE3 (ABI3), ABI5 and LATE EMBRYOGENESIS ABUNDANT (LEA) genes reminiscent of ABA signalling during early seedling development. ABI3 is a key regulator of the ABA-induced arrest and it is shown here that ABI3 functions in glucose signalling as well. Multiple abi3 alleles have a glucose insensitive (gin) phenotype comparable to that of other known gin mutants. Importantly, glucose-regulated gene expression is disturbed in the abi3 background. Moreover, abi3 was insensitive to sugars during germination and showed sugar insensitive (sis) and sucrose uncoupled (sun) phenotypes. Mutant analysis further identified the ABA response pathway genes ENHANCED RESPONSE TO ABA1 (ERA1) and ABI2 as intermediates in glucose signalling. Hence, three previously unidentified sugar signalling genes have been identified, showing that ABA and glucose signalling overlap to a larger extend than originally thought.